Structure activity relationships of anthranilic acid-based compounds on cellular and in vivo mitogen activated protein kinase-5 signaling pathways. Issue 13 (15th July 2018) - Chakrabarty, Suravi; Monlish, Darlene A.; Gupta, Mohit; Wright, Thomas D.; Hoang, Van T.; Fedak, Mitchel; Chopra, Ishveen; Flaherty, Patrick T.; Madura, Jeffry; Mannepelli, Shankar; Burow, Matthew E.; Cavanaugh, Jane E.
Graphical abstract: Highlights: Selective inhibition of MEK isoforms is possible with type III inhibitors. Omission of the requisite halogen bond to Val127 (MEK1) is tolerated at MEK5. Anionic anthranillate type III MEK inhibitors do not require an internal H-bond.